2019
DOI: 10.11646/zootaxa.4625.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The arctic and alpine bumblebees of the subgenus Alpinobombus revised from integrative assessment of species’ gene coalescents and morphology (Hymenoptera, Apidae, Bombus)

Abstract: The bumblebees of the subgenus Alpinobombus of the genus Bombus are unusual among bees for specialising in many of the most northerly vegetated arctic habitats on Earth. Most named taxa in this group (37 available names from a total of 67 names) were described originally from differences in the colour patterns of the hair. Previous revisions have shown unusually little agreement, recognising a range of 6‒9 species, in part because of pronounced intraspecific variation in both skeletal morphology and in the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 711 publications
(82 citation statements)
references
References 1 publication
4
78
0
Order By: Relevance
“…Some species historically described by discrete colour differences have been revealed to be conspecific, as discrete morphologies can be generated from diallelic Mendelian traits (Owen & Plowright, ; Rasmont et al ., ; De Meulemeester et al ., ). Failure to fully sort ancestral colour polymorphisms by species also has led to false inferences of species boundaries (Hines, ; Carolan et al ., ; Koch et al ., ; Williams et al ., ). In this instance, bifarius s.s. is a monomorphic red‐banded bee species and nearcticus is a polymorphic species that follows a continuum of variation from black to red from west to east (excepting island populations).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some species historically described by discrete colour differences have been revealed to be conspecific, as discrete morphologies can be generated from diallelic Mendelian traits (Owen & Plowright, ; Rasmont et al ., ; De Meulemeester et al ., ). Failure to fully sort ancestral colour polymorphisms by species also has led to false inferences of species boundaries (Hines, ; Carolan et al ., ; Koch et al ., ; Williams et al ., ). In this instance, bifarius s.s. is a monomorphic red‐banded bee species and nearcticus is a polymorphic species that follows a continuum of variation from black to red from west to east (excepting island populations).…”
Section: Discussionmentioning
confidence: 97%
“…Integrated approaches combining morphology, nuclear and mitochondrial sequences, and/or chemical data, are common for bumble bee species delineation (e.g. Lecocq et al ., ; Martinet et al ., ; Williams et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…It should be mentioned that according to Williams et al 2015Williams et al , 2019 polaris is found only in North America and Greenland, and is considered as a sister species of the Eurasian B. pyrrhopygus.…”
Section: Discussionmentioning
confidence: 99%
“…Based on genetic (Cameron et al, 2007) and morphological features (Richards, 1968;Ito, 1985), this subgenus is supported as a monophyletic taxon but the number of species is still debated mainly because authors follow different species concepts and/or methodologies (e.g. Williams et al, 2016Williams et al, , 2019Martinet et al, 2018;). Recent revisions on skeletal morphology, pheromones (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent revisions on skeletal morphology, pheromones (i.e. chemical traits) and genetic markers have concluded that there are from four to nine species, including cryptic species, in the last hypothesis (Martinet et al, 2018;Williams et al, 2019; Fig. 1).…”
Section: Introductionmentioning
confidence: 99%